2021
DOI: 10.1097/ta.0000000000003184
|View full text |Cite
|
Sign up to set email alerts
|

Four-factor prothrombin complex concentrate in adjunct to whole blood in trauma-related hemorrhage: Does whole blood replace the need for factors?

Abstract: BACKGROUND:The use of whole blood (WB) for the treatment of hemorrhagic shock and coagulopathy is increasing in civilian trauma patients. Four-factor prothrombin complex concentrate (4-PCC) in adjunct to component therapy showed improved outcomes in trauma patients.Our study aims to evaluate the outcomes of trauma patients who received 4-PCC and WB (4-PCC-WB) compared with WB alone. METHODS:We performed a 3-year (2015-2017) analysis of the American College of Surgeons-Trauma Quality Improvement Program databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Indeed, only 2.5% of blunt trauma patients in our study received WB in 2013 as compared with nearly five times that in 2016. This likely reflects the renewed interest in the benefits of WB resuscitation over blood component resuscitation recently demonstrated in the literature, including increased available hematocrit, and improved coagulation factor and platelet concentration and function 32–37 . Because previous work and our study have shown that balanced component therapy in ratios that mimic WB is associated with improved outcomes, transfusing WB may simply represent the logical end goal of trauma resuscitation practices.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, only 2.5% of blunt trauma patients in our study received WB in 2013 as compared with nearly five times that in 2016. This likely reflects the renewed interest in the benefits of WB resuscitation over blood component resuscitation recently demonstrated in the literature, including increased available hematocrit, and improved coagulation factor and platelet concentration and function 32–37 . Because previous work and our study have shown that balanced component therapy in ratios that mimic WB is associated with improved outcomes, transfusing WB may simply represent the logical end goal of trauma resuscitation practices.…”
Section: Discussionmentioning
confidence: 60%
“…This likely reflects the renewed interest in the benefits of WB resuscitation over blood component resuscitation recently demonstrated in the literature, including increased available hematocrit, and improved coagulation factor and platelet concentration and function. [32][33][34][35][36][37] Because previous work and our study have shown that balanced component therapy in ratios that mimic WB is associated with improved outcomes, transfusing WB may simply represent the logical end goal of trauma resuscitation practices. Future studies assessing the impact of the adoption of WB-based transfusion practices on a national scale are warranted.…”
Section: Discussionmentioning
confidence: 82%
“…The mortality was significantly lower in the military DoDTR population (23% vs 41%, P < 0.001). Military patients who survived had a discharge mean GCS of 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, 32 (32.7%) of them had a discharge GCS < 9.…”
Section: Resultsmentioning
confidence: 98%
“…In a prospective observational study, the CENTER-TBI and OzENTER-TBI groups showed that positive fluid balance in the setting of TBI was associated with negative effects on outcome. 11 As resuscitation goals have adjusted and management has shifted toward balanced component replacement 12 and now whole blood therapy 13 and even whole blood with concentrated factor adjuncts, 14 these resuscitation strategies have allowed for a reduction in the volume of resuscitation that may have a beneficial effect on ICP and outcome after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Across all nine observational studies, a total of 823 patients were included in the PCC treatment group (ranging from 9 to 234 patients per group). Two of the studies were multi-center with the remainder being single center [ 25 , 27 ]. The mean a 26 ge of the patients ranged from 36 to 51 years and the mean ISS from 23 to 50.…”
Section: Resultsmentioning
confidence: 99%